Appreciative student voice model – reflecting on an appreciative inquiry research method for facilitating student voice processes. Issue 5 (3rd September 2018) - Bergmark, Ulrika; Kostenius, Catrine
ABSTRACT: The aim of this paper is to describe and discuss Appreciative Inquiry (AI) as a research method to facilitate student voice in school research. The paper sets out a model for conducting AI in schools. The research questions identified are: What are the researcher's reflections when using Appreciative Inquiry in school research? What challenges and opportunities can be found when using Appreciative Inquiry in research processes with students? An application of the model will be presented and problematised. The conclusions indicate the importance of inviting students to participate in the process of defining research topics, and of using multimodal methods for facilitating students' exploration of school experiences. It is also vital that adults support students in imagining and articulating visions on how to improve the school, as well as plans designing for enacting visions. Finally, a 'whole school approach' is emphasised for contributing to sustainable appreciative student voice work in schools.